Laboratory-confirmed DR, pre-XDR, and XDR-TB cases reported in the Free State, South Africa, from 2019 to 2022, according to previous and updated WHO definitions - Miss Zothile Skosana; Miss Likhona Dingiswayo; Mrs Anneke Van Der Spoel Van Dijk (International Journal of Infectious Diseases)
Introduction: The global challenge of Tuberculosis (TB) control persists, particularly in addressing drug-resistant (DR) TB across regions. Over time, the rise in rifampicin (RIF/R) resistance, multi-drug resistant TB (MDR-TB, characterised until 2022 by RIF and Isoniazid (INH) resistance), pre-extensively drug-resistant (pre-XDR) (MDR and with either fluoroquinolone (FQ) or aminoglycoside resistance) and XDR-TB (defined as Pre-XDR including Bedaquiline (BDQ) and Linezolid (LZD)) has resulted in regimen changes and ultimately redefining DR-TB definitions. This study aimed to determine and classify the reported DR-TB cases, particularly pre-XDR and XDR-TB, isolated at Universitas TB Laboratory in the Free State region from 2019 to 2022 using previous and new definitions to facilitate comparison over time. Methods: A retrospective analysis of clinical samples/isolates routinely processed at the National Health Laboratory Service (NHLS), Tertiary Hospital Laboratory in Bloemfontein, Free State, spanning the years 2019 to 2022, used data from the NHLS Corporate Data Warehouse (CDW). The data included results from diagnostic assays namely Xpert MTB/RIF Ultra, Genotype MTBDRplus for first-line drugs (RIF and INH), Genotype MTBDRsl for second-line drugs (FQ's and aminoglycosides), and phenotypic drug susceptibility testing (pDST) to determine DR-, MDR-, pre- and XDR-TB. Results: In total, 1247 TB cases were reported between 2019 and 2022, with 266 (22.3%) RR, 214 (17.2%) MDR-TB, 23 (1.9%) pre-XDR and 89 (7.1%) XDR cases based on the WHO before 2023 definitions. The occurrence, based on the updated 2023 WHO definitions, was DR/RR 480 (38.5%), pre-XDR (RR and FQ resistance) 63 (5.1%) and XDR (RR plus BDQ) 5 (0.4%), respectively. Discussion: The identification of Pre-XDR and XDR cases in the current study, based on older definitions, remained relatively low and significantly decreased using 2023 WHO definitions. High RR resistance underscores the necessity of regimen changes, potentially reducing DR-TB numbers. Monitoring of newer drugs like BDQ and LZD may aid in controlling XDR resistance and updating the available data assisted in gaining an understanding of the documented DR-TB cases in the Free State province to combat TB effectively. Conclusion: This research added to our understanding of pre-XDR and XDR-TB cases reported in the Free State. Recently updated WHO definitions demonstrated relatively low pre-XDR and XDR-resistant TB cases reported, which might allow increased resistance monitoring.